"Do You Want Fries With That?": The McDonaldization of University Education—Some Critical Reflections on Nursing Higher Education. (July 2018) - Holmes, Colin; Lindsay, David
Public universities, as the predominant source of nurse education, serve an instrumental role as pressure mounts to produce large numbers of workready graduates to meet the needs of the labor market. Neoliberalism is recognized as the dominant political and economic philosophy across the globe, and new managerialist, corporatized practices, as its "organizational arms, " are ubiquitous within the higher education sector worldwide. Intersecting this agenda are dramatic developments in the way university courses are being conceived and delivered based upon the increasing integration of digital technologies. Given the radical transformations brought about by Web 2.0 technologies, it is timely to critically analyze current narratives shaping the teaching and learning agenda and their impact on the nature and quality of nursing higher education. This article draws on the "McDonaldization thesis" of George Ritzer, concepts from the work of the Italian philosopher Giorgio Agamben, Habermasian social theory, and critical pedagogy. It concludes with a short overview of possible outcomes of the new agenda, and some strategies for resistance. Although the focus is on Australia, it is relevant to other countries to the extent that they are facing similar challenges and undergoing analogous pedagogic transformations.